2016
DOI: 10.1136/vetreccr-2016-000372
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an outbreak of neonatal calf diarrhoea in a dairy herd

Abstract: Neonatal calf diarrhoea can have a severe impact on health and growth of the individual affected. It also leads to significant economic losses in herds with high disease incidence. This case report documents the investigation and follow-up of a dairy herd with increased incidence of neonatal diarrhoea and scours-related mortality of calves. It also reflects how managing the expansion of a herd inappropriately can cause several losses, particularly in young stock. Treatment of individual sick animals, correctiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…are among the most common enteropathogens isolated in cases of NCD, with a prevalence ranging from 15 to 59% (de la Fuente et al, 1999;Björkman et al, 2003;Gulliksen et al, 2009;Izzo et al, 2011b). Furthermore, several studies indicate that infection rates in young dairy calves with Cryptosporidium parvum are as high as 100% in some herds (de Graaf et al, 1999;O'Handley et al, 1999, Olson et al, 2004Abuelo, 2016), which we also observed in the present study. Only one drug, halofuginone lactate, is currently licensed for the prevention and treatment of cryptosporidiosis in calves in Australia.…”
Section: Pathogens Causing Diarrheasupporting
confidence: 82%
“…are among the most common enteropathogens isolated in cases of NCD, with a prevalence ranging from 15 to 59% (de la Fuente et al, 1999;Björkman et al, 2003;Gulliksen et al, 2009;Izzo et al, 2011b). Furthermore, several studies indicate that infection rates in young dairy calves with Cryptosporidium parvum are as high as 100% in some herds (de Graaf et al, 1999;O'Handley et al, 1999, Olson et al, 2004Abuelo, 2016), which we also observed in the present study. Only one drug, halofuginone lactate, is currently licensed for the prevention and treatment of cryptosporidiosis in calves in Australia.…”
Section: Pathogens Causing Diarrheasupporting
confidence: 82%
“…Throughout the world, RVA is reported to be the main viral cause of neonatal diarrhea in calves of dairy and beef cattle herds [1,21]. In this outbreak, 25% (6/24) of diarrheic calves evaluated were RVA positive in both single (n = 3, 12.5%) and mixed (n = 3, 12.5%) infections with aichivirus B.…”
Section: Discussionmentioning
confidence: 97%
“…In dairy cattle herds, neonatal diarrhea is considered one of the main infectious diseases in suckling calves worldwide [1,4]. Some classes of microorganisms, such as bacteria, protozoa, and viruses, are infectious agents and are considered determinants of neonatal diarrhea [9].…”
Section: Introductionmentioning
confidence: 99%
“…E. coli is an important causative agent which has shown antimicrobial resistance. 2 Commonly used antibiotic treatment can significantly contribute to immunosuppression in calves, increasing their susceptibility to infections. It may also increase bacterial resistance, making effective elimination of infections more difficult.…”
mentioning
confidence: 99%